Significant tetracycline hydrochloride degradation and electricity generation in a visible-light-driven dual photoelectrode photocatalytic fuel cell using BiVO4/TiO2 NT photoanode and Cu2O/TiO2 NT photocathode. (10th October 2019) - Lu, Ying; Chu, Yicong; Zheng, Wenzhuo; Huo, Mingxin; Huo, Hongliang; Qu, Jiao; Yu, Hongbin; Zhao, Yahui
Abstract: A visible-light responsive dual photoelectrode photocatalytic fuel cell (PFC) which was consisted of n-type BiVO4 /TiO2 nanotube (NT) photoanode and p-type Cu2 O/TiO2 NT photocathode was successfully constructed for hazardous organics decomposition with simultaneous power recovery. The characterization proved the incorporation of BiVO4 and Cu2 O not only increased the light harvesting efficiency of photoelectrodes but also improved their quantum yield, eventually exhibiting high photoelectrochemical performances. Significantly enhanced removal of tetracycline hydrochloride and electricity generation was obtained in the BiVO4 /TiO2 NT-Cu2 O/TiO2 NT PFC system. The rate constant of this dual photoelectrode PFC was 1.42 and 3.66 times as much as that of BiVO4 /TiO2 NT-Pt PFC and Pt–Cu2 O/TiO2 NT PFC, respectively, and the maximum power density was 1.68 and 103.8 folds as great as that of BiVO4 /TiO2 NT-Pt PFC and Pt–Cu2 O/TiO2 NT PFC. The enhancement was attributed to the large interior bias originated from the Fermi level difference between two electrodes, driving the photoelectrons of BiVO4 /TiO2 NT to combine with the holes of Cu2 O/TiO2 NT across external circuit and thus generating electricity. Meanwhile, organics were degraded by the anode holes, cathode electrons, and reactive oxygen species generated via chain reactions. The mechanism analysis confirmed the important roles of cathode electrons and anode holes, either acting as the oxidizing agent or the origination of hydroxyl radicals. Furthermore, the BiVO4 /TiO2 NT-Cu2 O/TiO2 NT PFC displayed good stability and reusability. Graphical abstract: Aiming at enhancing the hazardous organics decomposition and power recovery, a visible-light responsive dual photoelectrode photocatalytic fuel cell (PFC) consisted of n-type BiVO4/TiO2nanotube (NT) photoanode and p-type Cu2O/TiO2NT photocathode was successfully constructed. The proposed PFC system provided a self-sustained and energy-saving methodology for simultaneous pollutants removal and electricity generation.Image 1 Highlights: The BiVO4 /TiO2 nanotube (NT) photoanode was developed. The Cu2 O/TiO2 NT photocathode was developed. A visible-light-driven dual photoelectrode PFC was established. The PFC operated utilizing the Fermi level difference between two photoelectrodes. The PFC was efficient for electricity production and hazardous organics removal.